A sustainable fungal microbial fuel cell (FMFC) for the bioremediation of acetaminophen (APAP) and its main by-product (PAP) and energy production from biomass. (November 2019) - Pontié, M.; Jaspard, E.; Friant, C.; Kilani, J.; Fix-Tailler, A.; Innocent, C.; Chery, D.; Mbokou, S.F.; Somrani, A.; Cagnon, B.; Pontalier, P.Y.
Abstract: A fungal biofilm of Scedosporium dehoogii was successfully elaborated and used as a bio anode in a microbial fuel cell device. The cathode was a carbon felt electrochemically modified by electrodeposition of a film of poly-Ni(II) tetrasulphonated phthalocyanine (poly-NiTSPc). The elaborated biofilm, formed by electrodeposition of a suspension of Scedosporium dehoogii worked to catalyze acetaminophen (APAP) oxidation in the anode. The optimal potential during the electrodeposition process was found to be 0.8 V vs. saturated calomel electrode (SCE) with a thickness of 3.5 ± 0.2 μm. The fabricated fungal microbial fuel cell (FMFC) proved to be an efficient fuel in acetaminophen with highly stable output performances offering a power density of 50 mW m −2 under an electromotive force of +550 mV in physiological conditions. The biodegradation of PAP, the main APAP by-product from bacterial biodegradation, was also studied and the optimal resistance from the usual polarization curves was 3.000 Ohm. Finally, the biodegradation of ligno-cellulosic materials such as bagasse, rapeseed, cellulose and lignin by Scedosporium dehoogii was successfully tested in Petri dishes. The growth of the fungus using these biomaterials as substrates followed the order: bagasse > rapeseed > cellulose > lignin. The FMFC was tested in the presence of natural lignin from sugarcane bagasse and complete degradation of the lignin by S. dehoogii biofilm was achieved with a power density of 16 mW m −2 .